Employee Retention, Training and Development in Banking Sector: A Review Paper - Dikshit, Ashish; Kumar Jain, Trilok (Journal of Advanced Research in Operational and Marketing Management, 2023)
The government policy of less restriction in governmental regulations, liberalization, globalization and privatization have all contributed majorly towards Public Sector Banks in India to forcefully compete with Private and Foreign Banks. Organizational effectiveness can be achieved by Training and skill development of employees at various levels. Implementing Training and skill development programs in banks helps in running banking business effectively, and makes the banks prepared to cope up with changes and developments. Retention of employes with due compensation and reward system leads to commitment at work place, job satisfaction and motivation of employes. Further the bank implementation of Training and skill development for employe growth, their empowerment and environment of trust gives a competitive advantage due to the implementation of best HR Practices